The First Indoor Radon Gas Measurement at Historical Places in Cappadocia, Nigde, Turkey - Vakkas Bozkurt; Sefa Ertürk (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The aim of this study is todetermine the concentration of Radon and its annual effective dose at the NigdeMuseum and in a number of historical places namely the Sungur Bey, theAlaeddin, the Disari mosque and the Ak Medrese Culture House in Cappadocia,Nigde, Turkey by using a nuclear track detector CR-39 to ascertain how muchRadon concentration affects the people who are working in or visiting suchplaces. Nuclear track detectors CR-39 were used for measurement for 132 days atthe Nigde Museum, and for 63 days in the historical places. The exposed nucleartrack detectors were then sent to the Sarayköy Nuclear Research and TrainingCenter (SANAEM) to determine of Radon-222. The average Radon concentrationresults obtained for the Nigde Museum, the Sungur Bey, the Alaeddin, the Disarimosques and the Ak Medrese Culture House were 13.0±2.94 Bq/m3,31.67±3.86 Bq/m3, 52.0±5.72 Bq/m3, 42.67±19.34 Bq/m3and 31.0±4.55 Bq/m3 respectively. The average effective dose ofRadon was calculated for the Nigde Museum, the Sungur Bey, the Alaeddin, theDisari mosques and the Ak Medrese Culture House in Nigde and was found to beapproximately 0.137 mSv/y, 0.062 mSv/y, 0.103 mSv/y, 0.084 mSv/y and 0.327mSv/y respectively